Design vs Report: How Research Design Choices Predict Quality of Scientific Papers in Paper Writing Training - Naily Kamaliah; Alpha Fadila Juliana Rahman; Sutrisno Heru Sukoco; Dwi Indah Rahayu (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2025)
This study examines the alignment between planned research designs and final Scientific Paper (KTI) reports produced by participants of basic-level KTI training (N = 160 participants; 80 teams) during 2023–2024, and tests whether design elements and participants’ substantive understanding predict paper quality and presentation. We coded concordance between planned and implemented elements (problem formulation, data source, analysis method) and analyzed associations using Fisher’s exact tests, logistic regression for binary outcomes, and linear regression for presentation scores. Results show that 44.8% of teams produced KTIs fully concordant with their designs; 32.5% of teams moved from descriptive designs to include inferential analysis in final KTIs. Concordance of analysis method (design to implementation) was the only design element that significantly predicted substantive-quality scores (p = 0.029). Participants’ substantive-understanding scores predicted presentation quality (β = X, p = 0.013). We discuss implications for training curricula and recommend embedding method-focused mentoring and assessment checkpoints.